644 Risk factors for work related musculoskeletal disorders among physiotherapists. (24th April 2018) - Sharan, Deepak; Rajkumar, Joshua Samuel; Balakrishnan, Rajarajeshwari
Abstract : Introduction: Physiotherapists (PT) are highly predisposed to work related musculoskeletal disorders (WRMSD), due to their work nature involving manual effort, static holding and repetitive action. The severity of the WRMSD is reported to affect the quality of life causing sickness absenteeism to work, increased restrictions to work and disability. Hence, identifying the WRMSD at an early stage could help in reducing the morbidity among the PTs. Methods: A longitudinal survey was conducted among PTs through a semi-structured questionnaire administered by in-person or by E-mail. A total of 350 participants consented to participate in the study. The participants were working as full time PTs, with a minimum of 1 year of professional experience, age group 22 to 45 years, of either gender, who had pain or discomfort for more than one week, and did not undertake any other part time job. The PTs did not have any prior musculoskeletal disorders, surgeries, pregnancy within the previous 12 months or any systemic health problems. The questionnaire collected demographic data, exercise habits, physical risk factors associated with working condition, present health status, Nordic Musculoskeletal Questionnaire (NMSQ) and the short-form Workstyle Questionnaire. Result: The prevalence of musculoskeletal pain among PTs was found to be 88% and the highest prevalence of musculoskeletal pain was in the low back (61.5%) followed by upper back (59.25%). The mean age of the participants was 27.6 years. The prevalence of WRMSD was higher among male PTs (63%) and among those working in the paediatric neurorehabilitation department. 74% of the participants reported an adverse work style risk. Discussion: The high prevalence of WRMSDs among PTs can be attributed to several risk factors like lifting or transferring of dependent or non-communicative patients, work setting, practice specialty, age, gender, number of working hours, years of work experience and sedentary life style.